Treatment of esophageal cancer: surgical outcomes of 335 cases operated in a single center - FERREIRA,RAPHAELLA PAULA (2021)
ABSTRACT Objectives: the surgical approach persists as the main treatment for esophageal cancer. This study compares the patients of the same institution over time at three different times. Methods: this is a retrospective, observational, descriptive study comparing the surgical outcomes obtained by the Division of Surgical Oncology of Erasto Gaertner Hospital. The sample was divided into Period 1 (1987-1997), Period 2 (1998-2003) and Period 3 (2007-2015). Survival rates and disease-free survival were estimated by the Kaplan-Maier method. Survival predictors were identified with Cox regression. ANOVA test was used for comparison between groups. Data were analyzed with SPSS 25.0 and STATA 16, and p<0.05 was considered statistically significant. Results: a total of 335 patients underwent esophagectomy or esophagogastrectomy. When the clinical characteristics of the 3 groups were compared, there was no statistically significant difference. Neoadjuvance was significantly higher in Period 3 (55.4% of patients). We found a histological change in the diagnosis over time, with a significant increase in adenocarcinoma. Morbidity and mortality rates were higher in Period 3. The main complications were pulmonary and anastomotic fistulas. Overall survival in 5 years increased over time, reaching 59.7% in Period 3. Conclusions: better neoadjuvant treatment contributed to increase the global survival of patients, despite greater rate of immediate complications to surgery.